PAKISTAN-AFGHANISTAN RELATIONS AFTER 2021: THE ROLE OF EXTERNAL ACTORS AND CENTRAL ASIA (Eureka Journal of Humanities and Social Research, 2026)
The collapse of the Islamic Republic of Afghanistan in August 2021 and the Taliban’s return to power fundamentally transformed the geopolitical architecture of Central and South Asia. While the immediate Pakistan-Afghanistan borderlands face active conflict, this research monitors the changing roles of global powers and Central Asian neighbors in response to the shifting power dynamics. The study contends that external actors possess broader geopolitical significance beyond the bilateral Af-Pak tension. China pursued transactional engagement linked to regional connectivity and the China-Pakistan Economic Corridor, while Russia gradually expanded diplomatic relations with the Taliban government. Moreover, India adopted a pragmatic regional approach through alternative trade corridors such as Chabahar and reconciled with the new Taliban government. In the thesis, particular focus is given to Uzbekistan’s policy of regional economic connectivity, “extraordinary desecuritization,” and how these policies are institutionalized via the Trans-Afghan corridor and cross-border energy projects.
Keywords: Pakistan-Afghanistan relations, Taliban regime, external actors, Central Asia, Uzbekistan, regional economic connectivity, Trans-Afghan corridor, transboundary hydropolitics.